2003
DOI: 10.1007/s00464-002-9123-0
|View full text |Cite
|
Sign up to set email alerts
|

Role of angiotensin II under prolonged increased intraabdominal pressure (IAP) in pigs

Abstract: Our results suggest that the renal vasoconstriction associated with increased IAP is due to increased production of angiotensin II. The oliguria associated with increased IAP is probably due, at least partly, to increased reabsorbtion of sodium and water in the renal tubuli caused by increased tissue concentration of aldosterone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
14
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 20 publications
2
14
0
Order By: Relevance
“…This finding is in agreement with our results using an IAP of 30 mmHg [9]. We have earlier shown that the angiotensin II receptor antagonist losartan prevented increase in renal vascular resistance, improved renal blood flow, prevented the rise in aldosterone blood concentration, and increased the urinary output to baseline level during 3 h of increased IAP [10].…”
supporting
confidence: 95%
“…This finding is in agreement with our results using an IAP of 30 mmHg [9]. We have earlier shown that the angiotensin II receptor antagonist losartan prevented increase in renal vascular resistance, improved renal blood flow, prevented the rise in aldosterone blood concentration, and increased the urinary output to baseline level during 3 h of increased IAP [10].…”
supporting
confidence: 95%
“…Decreased blood flow and abnormal glomerular filtration and tubular functions are major consequences of a pneumoperitoneum 1,6 . In addition, hormonal changes centrally and peripherally coordinated lead to greater releases of renin, angiotensin and vasopressin, which act together during episodes of increased intraperitoneal pressure and affect renal activity 9 . Positive intraperitoneal pressures also cause increases in sympathetic activity regulated by baroreceptors and mediated by the effects of hypercapnia, which may lead to renal cortical vasoconstriction and its sequelae 10,11 .…”
Section: Discussionmentioning
confidence: 99%
“…tional factors that may affect renal function during pneumoperitoneum include direct compression of the renal parenchyma and renal vein (4,17), increased resistance in the renal vasculature (47), and release of vasoconstrictors, such as vasopressin, angiotensin II, catecholamines, and endothelin (ET)-1 (1,13). The latter is a very potent natural mammalian vasoconstrictor agent (25), acting on the cardiovascular and renal systems and other target organs by binding to two major types of receptors, ET A and ET B (2,25,36).…”
mentioning
confidence: 99%